(untitled) (Journal of Fiber Bioengineering and Informatics, 2008)
Temperature-sensitive polymer membranes were prepared by combination of shape memory hydrophilic polyurethane (SMPU) and thermo-sensitive poly(N-isopropylacrylamide-co-sodium acrylate) [poly(NiPAAm-co-SA)] hydrogel micro-particles through composite coating method. These two intelligent polymer components endowed the composite membranes with &#8220double switch&#8221 on the water vapor permeability. Poly(NiPAAm-co-SA) hydrogel micro-particles exhibited a reversible volume transition at lower critical solution temperature (LCST) around 34-36&#176C in the experiment. The size of gel particles varied more than 10-fold between temperature above and below LCST. It is likely acted as a sensor of temperature and as an switch to regulate the water vapor permeability of composite membranes. Moreover, there was also a dramatic increase in water vapor permeability (WVP) with an increase in temperature from 35 to 40&#176C for the shape memory hydrophilic polyurethane basement membranes. Two different procedures for WVP test were employed to simulate different application situations of the composite membranes. The temperature-sensitive water vapor permeability of composite polymer membranes was investigated by varying the content of hydrogel micro-particles. All of the temperaturesensitive membranes could have water vapor permeability controlled in response to temperature changes.